2013
DOI: 10.1111/trf.12075
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, safety, and tolerability of a solvent/detergent‐treated and prion‐safeguarded transfusion plasma in a randomized, crossover, clinical trial in healthy volunteers

Abstract: The LG plasma product was bioequivalent to its predecessor with respect to recovery of clotting factors and demonstrated comparable safety and tolerability in healthy volunteers. Both products compensated well for the loss of clotting factors after apheresis (NCT01063595).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Octaplas is now available with a dedicated prion reduction step by affinity chromatography (OctaplasLG, Octapharma AG) which has been shown to have similar profiles of ADAMTS13 activity and ULVWF to regular SDP 20. OctaplasLG has been used in healthy volunteers and appears to be equivalent to Octaplas in regard to clotting factor recovery and safety 21. Given its potential enhanced safety, prion-reduced SDP plasma may therefore become the product of choice in the future after its safety and efficacy has been further validated.…”
Section: Management Of Ttpmentioning
confidence: 99%
“…Octaplas is now available with a dedicated prion reduction step by affinity chromatography (OctaplasLG, Octapharma AG) which has been shown to have similar profiles of ADAMTS13 activity and ULVWF to regular SDP 20. OctaplasLG has been used in healthy volunteers and appears to be equivalent to Octaplas in regard to clotting factor recovery and safety 21. Given its potential enhanced safety, prion-reduced SDP plasma may therefore become the product of choice in the future after its safety and efficacy has been further validated.…”
Section: Management Of Ttpmentioning
confidence: 99%
“…OctaplasLG is used in different countries routinely since several years and a recently performed clinical trial showed that Octaplas as well as OctaplasLG compensate well for the loss of clotting factors after apheresis [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, the resulting product is totally bioequivalent to S/D plasma and shows comparable recovery of clotting factors and comparable safety and tolerability [13]. The change in the manufacturing process, where the S/D treatment is consistently reduced, produces increased plasmin inhibitor concentrations in the plasma product and significantly higher plasma concentrations of plasmin inhibitor after transfusion in vivo [14].…”
Section: The Methods Of Inactivationmentioning
confidence: 99%